Long Non-Coding RNA BANCR Promotes Endometrial Cancer Cell Proliferation and Invasion by Regulating MMP2 and MMP1 via ERK/MAPK Signaling Pathway - Danni Wang; Danbo Wang; Ning Wang; Zaiqiu Long; Xuemei Ren (Cellular Physiology and Biochemistry, 2016)
Background/Aims: Microarray screening had found BRAF-activated non-coding RNA (BANCR) was significantly upregulated in type 1 endometrial cancer (EC). This study aimed to assess the potential role of long non-coding RNA (lncRNA) BANCR in the pathogenesis and progression of type 1 EC. Methods: Quantitative reverse transcription polymerase chain reaction (qRT-PCR) was used to confirm the expression of BANCR in type 1 EC tissue, and analyze its clinical significance. In vitro, RNA interference (siRNA) was used to investigate the biological role of BANCR in type 1 EC. Results: qRT-PCR revealed that the expression of lncRNA BANCR was higher in type 1 EC (PIn vitro, knockdown of BANCR significantly suppressed proliferation, migration, and invasion of Ishikawa and HEC-1A cells, and significantly inhibited the ERK/MAPK signaling pathway that decreased MMP2 and MMP1 expression. Conclusion: BANCR is highly expressed in type 1 EC tissue and promotes EC-cell proliferation, migration, and invasion by activating ERK/MAPK signaling pathway that regulates MMP2/MMP1 expression. BANCR is expected to become a prognostic marker and therapeutic target in type 1 EC.